Penerapan Konseling Individual Teknik Person Centered Therapy dalam Mengatasi Kesulitan Belajar Siswa (Indo-MathEdu Intellectuals Journal, 2026)
This study was grounded in findings indicating a decline in academic achievement and various forms of learning difficulties originating from both internal and external student-related factors. The research aimed to examine the implementation of individual counseling services using the Person-centered therapy technique in addressing students’ learning difficulties at SMP Negeri 2 Gunungsitoli Idanoi. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The research subjects consisted of school counselors and students experiencing learning difficulties. Data were analyzed systematically through data reduction, data display, and conclusion drawing to ensure coherent and in-depth interpretation. The findings revealed that the implementation of individual counseling using the Person-centered therapy technique effectively assisted students in identifying the sources of their learning difficulties, enhancing self-awareness, and fostering greater motivation and responsibility in the learning process. A warm, empathic, and unconditionally accepting counseling relationship emerged as the key factor contributing to the success of the intervention. These results affirm that a person-centered approach represents an effective guidance and counseling strategy for improving students’ learning quality and supporting their sustained personal and academic development.